An Interactive Mobile Application to Enhance Travel Planning Using a User-Centric Approach: A UX Design Case Study - Nikam, Avishkar; Verma, Indresh Kumar; Ranade, Pranita (International Journal of Interactive Mobile Technologies (iJIM), 2025)
With the rise of digital platforms, planning and managing travel has become more difficult because many users still have trouble figuring out how to use all the different tools available to them. This study aims to design a mobile-phone-based application that simplifies and enhances the process of international travel and reduces the difficulties faced by the user due to the use of a variety of tools for international trips. A systematic methodology, starting with a literature review followed by in-person interviews with 30 participants to find out their pain points, was used in this study, which used both qualitative and quantitative methods. A competitive analysis of leading travel apps was also conducted to benchmark missing features and opportunities. Fifty participants then took part in usability testing to see how well the prototype worked. The system usability scale (SUS) and a retrospective think-aloud technique were both used to measure how users interacted with the system. The usability testing showed that overall user experience was favorable, with an average SUS score of 87.23, which means the usability was great. A study of the competitors’ products revealed that the current ones did not have features such as integrated maps, route planning, and real-time weather-based suggestions for customizing itineraries. In the survey of user satisfaction, 82% of people said they were very satisfied with the app’s easy-to-use interface and personalized travel suggestions. However, some people said the method for suggesting trips could be improved. Based on the results, it looks like the proposed app could make planning international trips easier. But better in-app navigation and adding onboarding guidelines for older users could make them even happier. Future work will focus on fixing these problems and getting more people to use it so that it can be used by more people.